PENGARUH KOMPENSASI, PELATIHAN, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DRIVER GRAB DI RW 01 KELURAHAN KELAPA DUA KECAMATAN KEBON JERUK JAKARTA BARAT - Muhamad Amar (2021)
This research is included in quantitative research which aims to analyze the effect of compensation, training and work motivation on job satisfaction of Grab Drivers in Rw01 Kelapa Dua Village, Kebon Jeruk District, West Jakarta. This study uses a Grab Driver in Rw01, Kelapa Dua, Kebon Jeruk, West Jakarta as a sample. The selected sample collection technique is probability sampling with the type of simple random sampling. This study obtained data from distributing questionnaires to 53 respondents. This research uses the SmartPLS 3.0 analysis tool. This study gives the results that (1) compensation has an effect on job satisfaction. (2) training has no effect on job satisfaction. (3) work motivation has no effect on job satisfaction